Analisa in Silico Kunyit (Curcuma longa) sebagai Inhibitor Murine Double Minute 2 Protein untuk Terapi Glioblastoma Multiforme - Benny Iswanto Pantoro; Nancy Margarita Rehatta; Siti Khaerunnisa; Anna Surgean Veterini; Yuani Setiawati (Oceana Biomedicina Journal, 2020)
Brain tumor consists of tumor which grows primarily from cells in the brain (primary brain tumor) or systemic tumor which metastasized into the brain (secondary brain tumor). From all types of primary brain tumor, Glioblastoma Multiforme is the most common and the most malignant tumor. In 85% of Glioblastoma Multiforme cases are found a molecular alteration of the tumor suppresor gene p53 pathway, which promotes current studies to focus on this pathway. One of the pathway that can be used as therapeutic model is through inhibiting the murine double minute 2 protein (MDM2), which in itself is a p53 inhibitor. Turmeric (curcuma longa) is one of the traditional plants which is commonly used as herbs and its extracts has been studied to have an anti-cancer properties. This study is an in silico study which evaluate the potential efficacy of turmeric extract as a murine double minute 2 protein inhibitor using AutoDock 4.2 based on the Lamarckian genetic algorithm principle. Docking result shows binding energy ranging from -4.81 kcal/mol to -2.34 kcal/mol, with curcumenol having the lowest binding energy and curcumin having the highest binding energy. This study may be used as a base in further study (consists of in vivo and in vitro) of turmeric extract and its effect as the therapeutic regiments for Glioblastoma Multiforme.